Cirrhosis of Liver and Diabetes Mellitus - Debsarma, Smita; Islam, Md Ziaul (Ibrahim Medical College Journal, 2013)
Diabetes mellitus is being recognized as a serious global health problem and frequently associated with cirrhosis of liver. The cross-sectional comparative study was conducted among 83 diabetic cirrhotic patients admitted in Gastrointestinal Hepatobilliary and Pancreatic Disorders Department of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders and 83 non-diabetic cirrhotic patients admitted in Gastroenterology and Hepatology Department of Bangabandhu Sheikh Mujibar Medical University, Dhaka to assess the relationship between cirrhosis of liver and diabetes mellitus. The study was carried out during the period of January to June, 2010 and data were collected through face to face interview and reviewing medical documents by using a semi-structured questionnaire and checklist. Male, Muslims and illiterate were predominant in both diabetic and non-diabetic cirrhotic patients. It was found that non-viral cirrhosis was much higher in older age group (51-60years) than in younger age group (41-50years) in comparison to viral cirrhosis and this difference was found statistically significant [÷2 (3)=20.97, p<0.001]. Association of non-viral cirrhosis was found with hyperglycemia [÷2 (1)=15.65, p<0.001], poor glycaemic control [÷2 (1)= 9.86, p<0.01] and longer duration of diabetes [÷2 (2) =9.51, p<0.01]. Non-viral cirrhosis was significantly higher (28.3%) among the diabetic patients than the non-diabetic patients who suffered more (28.3%) from viral [÷2 (1)=41.36, p<.001]. The study recommends for glycemic control by leading disciplined life and taking apposite therapy for prevention of non-viral cirrhosis among diabetic patients. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14734 Ibrahim Med. Coll. J. 2012; 6(2): 59-63